2008
DOI: 10.1111/j.1460-9592.2008.02459.x
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of propofol infusion use by paediatric anaesthetists in Great Britain and Ireland

Abstract: There is a wide variety in the use of propofol infusions by paediatric anaesthetists. The mechanisms underlying PRIS are poorly understood and require further work to ensure propofol infusions are used appropriately for anaesthesia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…Our patient tolerated several anesthetics with propofol infusion, and intraoperative laboratory evaluation during cardiac catheterization did not reveal any unexpected acidosis. Some clinicians administer glucose‐containing fluids during propofol infusion to avoid PRIS . Propofol impairs the mitochondrial electron transport chain in a dose‐dependent fashion, and it has been suggested that ensuring adequate serum glucose will balance the aerobic needs of the mitochondria and avoid PRIS .…”
Section: Discussionmentioning
confidence: 99%
“…Our patient tolerated several anesthetics with propofol infusion, and intraoperative laboratory evaluation during cardiac catheterization did not reveal any unexpected acidosis. Some clinicians administer glucose‐containing fluids during propofol infusion to avoid PRIS . Propofol impairs the mitochondrial electron transport chain in a dose‐dependent fashion, and it has been suggested that ensuring adequate serum glucose will balance the aerobic needs of the mitochondria and avoid PRIS .…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetic vaporizers and anesthetic machines including gas analyzers are nearly universally available, whereas infusion pumps or even target‐controlled infusion (TCI) systems and EEG‐based hypnotic monitoring are not. This may be the reason why, even today, only a minority of the pediatric anesthetists in the UK use TIVA (46). However, with the focus uniquely on simplicity and safety many advances in medicine would not have been possible.…”
Section: Total Intravenous Anesthesia In Pediatrics (By Martin Jöhr)mentioning
confidence: 99%
“…[6] This clinical entity has been described mainly in pediatric critical care patients and has been associated with prolonged use (>48 h) and high doses (>4 mg/kg/h). [7] Ondansetron is considered to be a safe class of medications for postoperative nausea and vomiting. [8] Takotsubo cardiomyopathy (TTC) is an acute cardiac syndrome mimicking elevated ST-segment myocardial infarction, characterized by transient regional wall motion abnormalities involving the apical and middle portions of the left ventricle in the absence of significant obstructive coronary disease.…”
Section: Discussionmentioning
confidence: 99%